Respuesta :

Answer:

k=3

Step-by-step explanation:

Given equation is

[tex]x^2+y^2 -6y-12=0[/tex]

First we move -12 to the other side by adding 12 on both sides

[tex]x^2+y^2 -6y =12[/tex]

We apply completing the square method to get square form (y-k)^2

Lets take coefficient of y and then divide it by 2

-6 divide by 2  is -3

Then we square it (-3)^2 = 9

We add 9 on both sides

[tex]x^2+y^2 -6y + 9=12+9[/tex]

[tex]x^2+(y^2 -6y + 9)=21[/tex]

Now we factor,  y^2 - 6y +9 is (y-3)(y-3)= (y-3)^2

[tex]x^2+(y-3)^3=21[/tex]

Now we compare with x^2 + (y-k)^2 = 21 and find the value of k

The value of k = 3